Mostly Smokers: Identifying Subtypes of Emerging Adult Substance Users. (14th October 2016) - Tzilos, Golfo K.; Reddy, Madhavi K.; Caviness, Celeste M.; Anderson, Bradley J.; Stein, Michael D.
ABSTRACT: Background: The concurrent use of marijuana and other substances among emerging adults (ages 18–25) is a major public health problem. This study examined if there are distinct subtypes of emerging adult marijuana users and if these are associated with demographic and substance use variables. Methods: The design was a cross-sectional interview with a community sample of 1, 503 emerging adults in the northeastern U.S. who reported last month marijuana use. We used latent class analysis (LCA) to identify distinct subtypes of emerging adults who used additional substances and examined predictors of the latent classes. Results: We identified three distinct classes of emerging adults who use substances: "mostly smokers" (those who primarily use marijuana and nicotine), "moderate users" (those who primarily use marijuana and/or heavy episodic alcohol), and "polysubstance users." Polysubstance users had higher probabilities of use of all assessed substances (e.g. cocaine, opiates, sleep medications, stimulants, synthetic marijuana, and inhalants) than the other two groups. Not being currently enrolled in school and male gender were associated with mostly smokers and polysubstance users group status. Conclusions: We identified a distinct group of emerging adult marijuana users who primarily smoke marijuana and cigarettes, suggesting that there could be a shared vulnerability for risk of co-occurrence.